Factor by grouping: ab-3a+4b-12

Expert Answers
justaguide eNotes educator| Certified Educator

The expression ab-3a+4b-12 has to be factored.


= a(b - 3) + 4(b - 3)

= (a + 4)(b - 3)

The factored form of ab-3a+4b-12 = (a + 4)(b - 3)

atyourservice | Student

ab-3a+4b-12 just find what they have in common


a(b-3) 4(b-3)

(b-3) (a+4) you can go even father if you want and get the main answer by setting the parenthesis equal to zero.

(b-3) = 0




Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question